Rectified photocurrent in a planar ITO/graphene/ITO photodetector on SiC by local irradiation of ultraviolet light. (11th September 2017) - Yang, Junwei; Guo, Liwei; Huang, Jiao; Mao, Qi; Guo, Yunlong; Jia, Yuping; Peng, Tonghua; Chen, Xiaolong
Abstract: A rectified photocurrent behaviour is demonstrated in a simple planar structure of ITO-graphene-ITO formed on a SiC substrate when an ultraviolet (UV) light is locally incident on one of the edges between the graphene and ITO electrode. The photocurrent has similar characteristics as those of a vertical structure graphene/semiconductor junction photodiode, but is clearly different from those found in a planar structure metal–graphene–metal device. Furthermore, the device behaves multi-functionally as a photodiode with sensitive UV photodetection capability (responsivity of 11.7 mA W −1 at 0.3 V) and a self-powered UV photodetector (responsivity of 4.4 mA W −1 at zero bias). Both features are operative in a wide dynamic range and with a fast speed of response in about gigahertz. The linear I – V behaviour with laser power at forward bias and cutoff at reverse bias leads to a conceptual photodiode, which is compatible with modern semiconductor planar device architecture. This paves a potential way to realize ultrafast graphene planar photodiodes for monolithic integration of graphene-based devices on the same SiC substrate.